Formulasi Patch Ekstrak Etanol Daun Murbei (Morus Alba L.) dengan Variasi Konsentrasi Polimer Polivinil Pirolidon dan Etil Selulosa - Aisyah Fatmawaty; Michrun Nisa; Irmayani Irmayani; Sunarti Sunarti (STIFA Makassar, 2017)
Patch formulation studies have been conducted mulberry leaf extract with various concentrations of polyvinyl pirilidon and ethyl cellulose (EC) obtain a patch with good physical characteristics. Physical evaluation includes weight, thickness, and folding endurance, loss on drying and moisture uptake. The results showed that the optimum formula by solvent evaporation method is F3 (PVP : EC = 200 : 400) with average weight (0,76±0.006 g), resilience fold (> 200), thickness (0.411±0.039 cm), drying shrinkage (38.12 > 9.29 ) and absorption (29.06 > 9.79 ).